Sumbangan Ahl Al-Hadith Dan Peranannya Dalam Membangun Ketamadunan Islam - Yahya, M. A. (Universiti Sains Islam Malaysia, 2024)
The incident of the death of Caliph Uthman marks a new era in hadith history. The status of hadith and its acceptance amongst Muslim has become a centre of disputation and leads to the development of a new methodology in assessing hadith as invented by ahl al-hadith. This new method has its own roles and contributions in preserving the authenticity and provide a novel approach in vindicating a hadith as a major source of Islamic jurisprudence and its civilisation. This study explore the contribution of hadith as a source of Islamic civilisation, the role of ahl al-hadith in preserving the authenticity of hadith and their methods to substantiate hadith originality. The present study employed textual analysis as its main approach of investigation in this study. The study in its findings confirms the role of hadith and contribution of ahl al-hadith in the development of Islamic civilisation and society.